Socio-Economic Determinants of Health and Identification of Vulnerable Groups in the Context of Migration. The Case of Austria - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2003)
There are marked differences in health conditions of the Austrian population by socioeconomic status, gender, age, education, occupation and income as well as by nationality. The low educational attainment of migrants, their concentration in particular occupations and industries and their above-average unemployment rate, are associated with an aboveaverage morbidity rate of middle aged and older migrants. In addition, migrants exhibit another pattern of diseases than natives. They suffer to a greater extent than Austrians, from heart diseases, allergies, digestive and urogenital and dermatological problems. This may be partly the result of the particular stress situations they face in the work place and the community at large. The community in Austria and particularly in Vienna, face not only the challenge of the socioeconomic integration of largely less skilled migrants but also of providing adequate health services not only for the ageing Austrian population but also for an ageing migrant population.
Keywords: 330; Sozialer Status; Gesundheit; Schätzung; Österreich; Migranten